Community Capacity-Building in Schools: Parents’ and Teachers’ Reflections From an Eating Disorder Prevention Program - Russell-Mayhew, Shelly; Arthur, Nancy; Ewashen, Carol (Alberta Journal of Educational Research, 2008)
A pilot research study to examine the effect of a wellness-based intervention on improving students’ body image, personal attitudes, and eating behaviors highlighted the importance of a healthy school environment. Parent and teacher focus groups were conducted to explore the perceived influences of wellness-based interventions designed for parents, teachers, and students. Results support movement toward wellness-based programming and suggest that school-community capacity-building may be a worthwhile framework for continued study in relation to programming to prevent eating disorders. Excerpts from focus group data illustrate key themes in relation to change and demonstrate the importance of capturing both the content of the wellness-based interventions and the process of interaction in the schools. This pilot study found that interventions in schools that focus on wellness and target parents, teachers, and students are effective in terms of building capacity for promoting positive change in students’ attitudes and behaviors.